Retention of the highly skilled individuals educated in Finland : Case study of Vietnamese students’ perceptions of staying in Finland - Vu, An (My University, 2020)
Globalization has brought the global mobility phenomenon closer to the entire world. It indicates the movement of the labor force across borders. Thus, International Human Resource Management has become more and more important in recruiting and managing this source of labor force. This study examines factors affecting the willingness to relocate in Finland of Vietnamese with Finnish higher education experience. It strengthens and develops the studies on global mobility of the highly skilled individuals, focuses on three respondent groups which are oversea experience, self-initiated expatriates, and migration. To serve the purpose of this study, the factors are reviewed from global mobility related literature, and generated into applicable hypotheses. The hypotheses are then tested by quantitative method with the help of SPSS computer software. The study was conducted using an internet survey about willingness to relocate in Finland and received 106 valued answers of Vietnamese with Finnish higher education experience. Correlation, Independent t-Test, and basic data analysis were used to evaluate the result. The outcome of the study confirms the influence of social, career, family, education, culture, partners, and location factors on the willingness to relocate in Finland of Vietnamese respondents. Gender, previous oversea experience, age, and income were found partly influencing partner factors. Moreover, this study suggests language barrier, weather conditions, and passport power can also contribute to the overall willingness to relocate of the highly skilled. In general, self-initiated expatriates and migration groups are willing to relocate in Finland, but the result does not apply to the oversea experience group. Also, crucial implications are presented for not only companies’ managers but policy makers to help dealing with global mobility challenges.